Plasticity of growth rates and sizes at sexual maturity in different populations of the fiddler crab Minuca vocator (Herbst, 1804) within the same latitudinal range - Delevati Colpo, Karine (2022)
The growth rates and size at maturity of decapod crustaceans usually vary throughout latitudes. Here, we evaluated whether these life history traits can be stable within the same latitude range, where some environmental factors are constant, especially temperature. To this end, we estimated and compared the growth rates and size at sexual maturity of three populations of the fiddler crab Minuca vocator, located at latitude 23° S, in mangroves of the subtropical Brazilian coast. Variations in the growth rate of the abdominal width of females and of the propodus of the major cheliped of males were assessed by the allometric technique. The abdomen growth rates of females and the cheliped growth rates of males varied among the three populations, resulting in different sizes at maturity. These results do not support our prediction that growth rates and size at sexual maturity would remain stable in populations of the same latitude range. The differences in these life history traits could be a consequence of contrasting local conditions among mangroves. Therefore, we suggest that these crabs show plasticity and responsiveness to local-scale environmental variations, to optimize the energy allocation for maintenance, reproduction, and somatic growth.